Analysis of Commuter Route Passenger Train Station Moda -Station Lamongan Station, Turi Market Surabaya - Alfi, Numan; Mudjanarko, Sri Wiwoho (Universitas KH. A. Wahab Hasbullah, 2017)
Surabaya is a very influential on the increase in freight transportation needs of the surrounding city. Lamongan and Gresik city, which is access to Surabaya from western requiring rail transport. The city stands in many industrial plants that have large numbers of workers to transport large capacity that is expected to reduce the congestion of the city using Commuter Rail transport modes. Problem magnitude transport capacity makes researchers need to conduct research to analyze the commuter railway passengers who were in St. Lamongan. Method of research done in the form of a commuter passenger survey for analysis and calculation. The results of this study clearly visible that the respondent data penmpang 100 commuter trains, 75% of whom are of childbearing age, traveling on official business purpose. and the results of the CSI shows 44.78% of consumers rated less satisfied with the performance and service.